Purgatory Ridge : a novel - Krueger, William Kent (Krueger, William Kent. Cork O'Connor mystery., 2009)
Cork O'Connor is called in to investigate when a deadly explosion rocks the lumber mill of Karl Lindstrom, a wealthy, anti-environmentalist industrialist, whose mill is near an ancient tract of pine forest sacred to the Anishinaabe tribe.